Dispositive-disposition dyads as a lever for change-making: the reconfiguration of school spaces promoted by the Metropolitan Regeneration Program of Bologna - Baioni, Mauro (AESOP, 2024)
The paper discusses the modernization of school facilities, to address contemporary educational and social demands, as a critical issue for the public sector. The study focuses on the "Progetto Scuole Terre di Pianura," part of the Metropolitan Regeneration Program in Bologna, which aims to reconfigure school spaces to foster educational and social initiatives. The paper critically examines how public officials (disposition) engage with technical and regulatory frameworks (dispositive) to implement local projects. It underscores the crucial role of public officials in interpreting and applying these frameworks to achieve effective urban regeneration, navigating the complexity of public administration in resource-constrained environments. Keywords: City-education relationship Territorial governance Public action Small and medium-sized towns
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024